Relationship Between Age Level And Menstrual Status With Knowledge About Treatment Of Female Genetalia Organs - Annisa, Fausiyah; Irmawati, Irmawati; Riswan, Riswan (Sean Institute, 2022)
Menstruation is periodic vaginal bleeding due to the detachment of the endometrial lining of the uterus. The normal age for a woman to menstruate for the first time is at the age of 12 or 13 years. The aim of this study was to determine the relationship between age level and menstrual status with knowledge about the care of female genetal organs in Je'ne Madinging village, Gowa district.The method used is quantitative research with analytical survey design with a cross sectional approach using a questionnaire. the number of samples is 54 respondents. The study used the chi square test with a significance of 95% (p<0.05). The results obtained are as follows: There is a relationship between the level of age and knowledge about the care of female genetal organs P value =0.000 with a significance level of α = 0.05. Meanwhile, there was no correlation between menstrual status and knowledge about the care of female genetal organs. P value = 0.173 with a significance level of α = 0.05. Based on the results of the study, the researchers assumed that age was a factor related to the level of knowledge. Meanwhile, menstrual status is one of the factors that is not related to the level of knowledge. Suggestions: 1) For nursing services it can be input and reading material to increase knowledge 2) For the development of nursing science to increase knowledge and experience in reproductive health nursing research 3) For nursing research the results of this research are expected to be a source of reading material and comparisons for next researcher.